4-Chloro-N-(2-chlorobenzoyl)benzenesulfonamide - Gowda, B. Thimme (International Union of Crystallography, 2010)
In the structure of the title compound, C(13)H(9)Cl(2)NO(3)S, the conformation of the N—H bond in the C—SO(2)—NH—C(O) segment is anti to the C=O bond. The molecule is twisted at the S atom with a torsion angle of 65.7 (2)°. The dihedral angle between the sulfonyl benzene ring and the —SO(2)—NH—C—O segment is 88.5 (1)°, and that between the sulfonyl and the benzoyl benzene rings is 58.0 (1)°. In the crystal, molecules are linked by pairs of N—H⋯O hydrogen bonds, forming inversion dimers.